The fate of Shokha quartzite as a building and decorative stone - Shekov, Kirill; Shekov, Vitali (Wykorzystanie kwarcytu Shoksha jako kamienia budowlanego i dekoracyjnego, 2017)
The background of crimson quartzite, a unique stone with properties second to none, is discussed. The wide use of the stone in the past has made it famous, but the area where it was and is quarried has not become a monument. The authors wish to attract the attention of the reader to this area and to establish a mining and industrial park nearby.
Hereditas Minariorum, Vol. IV, 2017, s. 171-182
Keywords: górnictwo; historia; kultura materialna; archeologia przemysłowa; mining and industrial heritage; geological monuments; quartzite; Shoksha porphyry; decorative stone; dimension stone quarries; Republic of Karelia; Russia